The subconscious world of man. Imagination and its meaning - Khasanova Barno Jaloladdinovna; Juraeva Nigora Davronovna; Ochilova Lobar Sherali qizi; Rakhimova Dilorom Orifjonovna (Zien Journals, 2022)
Man differs from other beings by the presence of human thinking and can think consciously. This article discusses the secrets of the human subconscious world, which includes such concepts as contemplation, thinking, thought, imagination and perception. The imagination, its formation and significance are analyzed.
Keywords: subconscious world; thinking; thought; imagination